2012
DOI: 10.1074/jbc.m112.362210
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Acyltransferase Domain of the Iterative Polyketide Synthase in Enediyne Biosynthesis

Abstract: Background: DynE8 is an iterative polyketide synthase (PKS) that assembles polyketide intermediates from acetate units derived from malonyl-CoA. Results: We report the first acyltransferase (AT DYN10 ) crystal structure for an iterative PKS. Conclusion: AT DYN10 protects the malonyl-enzyme, but not the acetyl-enzyme intermediate, from hydrolysis and facilitates the transfer of malonyl to the acyl carrier protein.Significance: This differs from the dual specificity exhibited by acyltransferases of mammalian FAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 46 publications
3
51
0
Order By: Relevance
“…One of the top models was chosen on the basis of the alanine scanning mutagenesis data described above (Figure 6A). Overall, the docking model resembles that of the iterative type I PKS DynE8 AT and ACP (Liew, et al, 2012), and also that of the AT3-ACP3 model from DEBS (Wong, et al, 2010). ACP5 Kir is predicted to sit in a large cleft formed by parts of the KS-AT linker domain, as well as the small and large subdomains.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…One of the top models was chosen on the basis of the alanine scanning mutagenesis data described above (Figure 6A). Overall, the docking model resembles that of the iterative type I PKS DynE8 AT and ACP (Liew, et al, 2012), and also that of the AT3-ACP3 model from DEBS (Wong, et al, 2010). ACP5 Kir is predicted to sit in a large cleft formed by parts of the KS-AT linker domain, as well as the small and large subdomains.…”
Section: Resultsmentioning
confidence: 90%
“…This is in agreement with phylogenetic analyses, which showed that KirCII is more closely related to cis-AT’s than to malonate-specific trans-ATs (Musiol and Weber, 2012). In addition to the large and small AT subdomains typical of trans-AT’s, the modeled KirCII structure also includes a KS-AT linker domain that is usually associated with cis-acting AT domains from type I PKSs (Liew, et al, 2012; Tang, et al, 2006). This prediction is in agreement with the sequence length of KirCII (which is longer than that of DSZS and MCAT), homology between the N-terminal portion of KirCII and various cis-AT’s (Figure S3), in addition to secondary structure similarity between the predicted KirCII KS-AT linker and structure of a known linker domain (Figure S4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, S. coelicolor MCAT was suggested to interact with the loop region between helix I and II of actinorhodin PKS ACP (19,29). Alternatively, the presence of an additional domain such as the KS-AT linker domain in modular PKS might be involved in the binding mode of ACP, as proposed in the interaction between AT DYN10 and ACP DYN involved in dynemicin biosynthesis (30). For complete understanding of ACP recognition by AT, it is necessary to obtain other AT-ACP complex structures.…”
Section: Discussionmentioning
confidence: 99%